Analyzing Electronic Medical Record Adoption by Registra-tion Staff Using TAM at Tangkiling Health Center, Palang-ka Raya - Nia Kurniati; Wahyu Wijaya Widiyanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study investigates the adoption of Electronic Medical Records (EMR) by registration staff at Tangkiling Health Center, Palangka Raya, using the Technology Acceptance Model (TAM) framework. Out of 61 total healthcare workers, five medical record staff with educational backgrounds in midwifery, nursing, dental nursing, and non-medical high school were purposively selected as research participants. The study employed a qualitative descriptive method, combining in-depth interviews and direct field observations. Results indicate that while the staff acknowledged the usefulness of EMR in improving service efficiency and data accessibility, several barriers hindered its effective use—primarily a lack of training, limited digital literacy, unstable internet connectivity, and inadequate hardware such as computers and printers. Observations showed that only the registration unit had a single shared computer, while other units like outpatient clinics, pharmacy, and cashier still relied on manual documentation. This fragmentation has led to duplicate workloads and disrupted patient data continuity. Despite these challenges, the staff demonstrated a positive attitude and strong behavioral intention to adopt EMR if provided with sufficient infrastructure and regular training. The study concludes that successful EMR implementation in primary healthcare requires not only user acceptance but also institutional readiness, adequate resources, and integrated systems across all service units.